1972
DOI: 10.1104/pp.50.1.185
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Metal Porphyrins by Subchloroplastic Fractions

Abstract: The biosynthesis of Mg protoporphyrin monoester, protochlorophyll and chlorophyll a and b by crude homogenates, isolated etioplasts, and differentiating chloroplasts has recently been described by . In the present communication we wish to report briefly on the capacity of subchloroplastic fractions to form free porphyrins and metal porphyrins. MATERIALS AND METHODSCucumber seeds (Cucumis sativus L. cv. Alpha Green) were germinated in vermiculite (Terra Lite) at 24 C in complete darkness for 4 days (7,8). Cotyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 9 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…Carell & Kahn (18) showed that a substantial propor tion of the chloroplastic enzyme remained bound to the membranes of lysed and washed mature Euglena chloroplasts. On the other hand, Rebeiz et al reported that most of the free porphyrin biosynthetic activity of greening etioplasts was found in the soluble fraction (supernatant of the centrifugation at 105,000 g) of the lysed plastids (127). The green membrane fraction exhibited very little por phyrin biosynthetic activity when incubated with ALA.…”
Section: Formation Of A-aminolevulinic Acidmentioning
confidence: 97%
“…Carell & Kahn (18) showed that a substantial propor tion of the chloroplastic enzyme remained bound to the membranes of lysed and washed mature Euglena chloroplasts. On the other hand, Rebeiz et al reported that most of the free porphyrin biosynthetic activity of greening etioplasts was found in the soluble fraction (supernatant of the centrifugation at 105,000 g) of the lysed plastids (127). The green membrane fraction exhibited very little por phyrin biosynthetic activity when incubated with ALA.…”
Section: Formation Of A-aminolevulinic Acidmentioning
confidence: 97%
“…was vacuum-filtered through an asbestos-coated funnel, and the residue was resuspended volume of the extraction solution and filtrates were combined and the residue, fluorescent, was discarded. The combined with an equal volume of petroleum ether [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] to remove Crystalline standards of copro and proto methyl esters were hydrolyzed in 3 N HCl for 12 hr. This yielded a mixture of partial esters as chromatographic standards (20).…”
mentioning
confidence: 99%
“…4 (3,17,18). The same appears to be true whenever the normal flow of the chlorophyll biosynthetic pathway is blocked or damaged by incubation in the absence of cofactors (Table III) or by lysis and fractionation of the developing chloroplasts (16). So far it has been possible to show a net chlorophyll biosynthesis in vitro for limited periods of incubation.…”
Section: Discussionmentioning
confidence: 81%
“…Chlorophyll a + b was prepared from greening cucumber cotyledons and purified by thin layer chromatography as previously described (10). A subchloroplastic soluble enzyme system (S3) capable of uro, copro, and protoporphyrin biosynthesis and accumulation was prepared from developing chloroplasts (16). It was incubated with 25 ,imoles of ALA and cofactors for 16 hr, as described in a previous communication (16).…”
mentioning
confidence: 99%